Effects of environmental bisphenol S exposure on male rat reproductive health and gut-blood-testicular axis integrity - Biran Zhu; Zequan Zhang; Ying Xie; Min Huang; Yu Chen; Yong Yang; Xiongjie Shi; Jian Han; Lihua Yang; Min Zhao (Ecotoxicology and Environmental Safety)
In this study, male Sprague–Dawley (SD) rats were exposed to bisphenol S (BPS) at environmentally relevant concentrations to investigate its reproductive toxicity and evaluate its effects on the gut-blood-testicular axis. After 28 days of exposure to BPS (0.05 and 20 mg/kg), the results showed a reduction in weight gain and the induction of reproductive toxicity in male rats, including decreased sperm parameters, lower sperm viability, and increased abnormal sperm density and mortality. These observations were made by counting with a hemocytometer under the optical microscope. 16S rRNA and untargeted metabolomic elucidated potential impacts on the gut-blood-testicular axis: BPS impaired the physical barrier, evoked inflammation, and resulted in dysbiosis of the gut microbiota. Additionally, BPS altered serum metabolites, including phosphatidic acid and diacylglycerol, which are involved in Fc gamma R-mediated phagocytosis and linked to inflammation. Furthermore, histopathological analysis, western blot (WB), enzyme-linked immunosorbent assay (ELISA), and immunofluorescence results showed that exposure to BPS led to testicular damage, inflammation, activation of the p38 and ERK MAPK pathways, and disruption of the blood-testis barrier (BTB). Collectively, these findings indicate that BPS impair the intestinal health, disrupt gut microbiome, and ultimately lead to reproductive dysfunction through the gut-blood-testicular axis.